CHRISTOFFEL VAN SICHEM’S ENGRAVER’S WORKS IN ARMENIAN ART (Bulletin of Armenian Libraries, 2025)
In the 16th centuries in the Armenian cultural life, an extremely important event took place, the start of Armenian printing. After the Gutenberg invention, a rapidly developing printingbusiness in Europe drew the Armenian cultural figures’ attention. Until 18th century the Armenian printed books were used by the works of European engraving masters, especially the German motifs by Christoffel van Sichem.